Failure to repair damaged NAD(P)H blocks de novo serine synthesis in human cells - Adhish S. Walvekar; Marc Warmoes; Dean Cheung; Tim Sikora; Najmesadat Seyedkatouli; Gemma Gomez-Giro; Sebastian Perrone; Lisa Dengler; François Unger; Bruno F. R. Santos; Floriane Gavotto; Xiangyi Dong; et al. (Cellular & Molecular Biology Letters)
Abstract Background Metabolism is error prone. For instance, the reduced forms of the central metabolic cofactors nicotinamide adenine dinucleotide (NADH) and nicotinamide adenine dinucleotide phosphate (NADPH), can be converted into redox-inactive products, NADHX and NADPHX, through enzymatically catalyzed or spontaneous hydration. The metabolite repair enzymes NAXD and NAXE convert these damaged compounds back to the functional NAD(P)H cofactors. Pathogenic loss-of-function variants in NAXE and NAXD lead to development of the neurometabolic disorders progressive, early-onset encephalopathy with brain edema and/or leukoencephalopathy (PEBEL)1 and PEBEL2, respectively. Methods To gain insights into the molecular disease mechanisms, we investigated the metabolic impact of NAXD deficiency in human cell models. Control and NAXD-deficient cells were cultivated under different conditions, followed by cell viability and mitochondrial function assays as well as metabolomic analyses without or with stable isotope labeling. Enzymatic assays with purified recombinant proteins were performed to confirm molecular mechanisms suggested by the cell culture experiments. Results HAP1 NAXD knockout (NAXDko) cells showed growth impairment specifically in a basal medium containing galactose instead of glucose. Surprisingly, the galactose-grown NAXDko cells displayed only subtle signs of mitochondrial impairment, whereas metabolomic analyses revealed a strong inhibition of the cytosolic, de novo serine synthesis pathway in those cells as well as in NAXD patient-derived fibroblasts. We identified inhibition of 3-phosphoglycerate dehydrogenase as the root cause for this metabolic perturbation. The NAD precursor nicotinamide riboside (NR) and inosine exerted beneficial effects on HAP1 cell viability under galactose stress, with more pronounced effects in NAXDko cells. Metabolomic profiling in supplemented cells indicated that NR and inosine act via different mechanisms that at least partially involve the serine synthesis pathway. Conclusions Taken together, our study identifies a metabolic vulnerability in NAXD-deficient cells that can be targeted by small molecules such as NR or inosine, opening perspectives in the search for mechanism-based therapeutic interventions in PEBEL disorders. Graphical Abstract